The Effects of Regional and Industry: Wide FDI Spillovers on Export of Ukrainian Firms - Sang-Min Park; Oleksandr Talavera; Stefan Lutz (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
In this paper we investigate the effects of region and industry?wide spillovers from foreign direct investment (FDI) on the volumes of export of Ukrainian manufacturing firms, using unpublished panel data from 1996?2000. Economic theory suggests that FDI has direct and indirect effects on firm?s performance. Our analysis focuses on the indirect effects like competition and linkage effects through industrial and regional spillovers respectively. We use a simple Cournot competition model in order to test for industrial and regional spillovers. The estimation results suggest that large firms, durable?goods makers, and firms located in urban areas benefit most from FDI spillovers.
Keywords: L60; F23; 330; transition economies; Ukraine; foreign direct investment; spillovers; Direktinvestition; Spillover-Effekt; Verarbeitendes Gewerbe; Export; Außenhandelswirtschaft; Monopolistischer Wettbewerb; Schätzung; Ukraine